2011
DOI: 10.1016/j.corsci.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of nanocomposite TiSiN coatings on steel substrates

Abstract: Nanocomposite TiSiN coatings were deposited on tool steels. Detailed mechanisms that govern the corrosion of these coated steels were revealed, following immersion tests in a 70% nitric acid solution. Pitting originated preferentially from coating defect sites and expanded with increasing immersion time. Both Young's modulus and hardness measured by nanoindentation decreased as the corrosion damage intensified. A thin oxide layer formed from the thermal annealing of the as-deposited samples at 900 C was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…3. Obviously, the main peak of all the CrSiCN coatings could be deconvoluted into two overlapped peaks related to Si-C bond around 101.1 eV and Si-N bond around 101.8 eV [24,[39][40][41]. Moreover, the volume fraction of Si-N bond increases with increasing Si concentration, and finally a novel and weak Si-Si bond presents at 99.2 eV due to higher Si incorporation in CrSiCN (30) …”
Section: Element Concentration and Phase Condition Of Coatingsmentioning
confidence: 96%
“…3. Obviously, the main peak of all the CrSiCN coatings could be deconvoluted into two overlapped peaks related to Si-C bond around 101.1 eV and Si-N bond around 101.8 eV [24,[39][40][41]. Moreover, the volume fraction of Si-N bond increases with increasing Si concentration, and finally a novel and weak Si-Si bond presents at 99.2 eV due to higher Si incorporation in CrSiCN (30) …”
Section: Element Concentration and Phase Condition Of Coatingsmentioning
confidence: 96%
“…(c) and (d)], Cr 2 O 3 was dominant on the CrN coating surface and can effectively seal corrosion pathways (i.e., structural defects) and thus imparting to the coating a greater corrosion resistance. According to the observation of structural defects in the coatings and XPS data, a model was proposed to elucidate the role of the oxide layer in amending surface defects and restoring the structural integrity (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…18 For the uncoated steel sample, widespread intergranular corrosion was observed after electrochemical testing in both solutions [ Fig. 6(a) in the coatings 24 and XPS data, a model was proposed to elucidate the role of the oxide layer in amending surface defects and restoring the structural integrity (Fig. 7).…”
Section: (3) Electrochemical Measurementsmentioning
confidence: 99%
“…M.S. Ahmed et al [16] reported that the oxide layer formed from coatings surface and reduction of residual stress could increase the corrosion resistance of TiSiN coatings after 900 o C annealing. In addition, the nano-composite and multilayer structures, incorporation of the interlayer (such as PVD Al, Si etc.)…”
Section: Introductionmentioning
confidence: 99%